ВПЛИВ СЕМАНТИКИ КОМПОНЕНТІВ У МОДАЛЬНИХ ДІЄСЛІВНИХ КОНСТРУКЦІЯХ З МОДАЛЬНІМИ ДІЄСЛОВАМИ «ПОВИННОСТІ» НА ЇХ ГРАМАТИЧНІ ТА СТАТИСТИЧНІ ОСОБЛИВОСТІ (НА МАТЕРИАЛІ ТЕКСТІВ ТЕХНІЧНОГО ДИСКУРСА) - Борисенко , Т.; Цинова, М.; Цапенко , Л.; Сиротенко, Т. (ПРОБЛЕМИ СЕМАНТИКИ, ПРАГМАТИКИ ТА КОГНІТИВНОЇ ЛІНГВІСТИКИ, 2023)
У статті представлено дослідження модальних дієслівних конструкцій з модальними дієсловами "повинність", must, have to+inf. Be to+inf., які функціонують в трьох технічних текстових корпусах і належать до технічних областей, не пов’язаних один з одним. Семантичні особливості аналізуються та порівнюються з граматичними та статистичними. Спостерігаються взаємозв’язки цих трьох характеристик у кожному компоненті, а також взаємозалежність між кожним компонентом модальних конструкцій дієслова в семантиці, граматиці та статистиці. Але домінуючою характеристикою є семантика. __________ References Dictionary by Merriam-Webster (Learners’ Dictionary). Available at http://learnersdictionary.com/ Grebneva O. V. The modality of necessity in the legislative acts of European Union: dis. abstract for the Candidate of Philological Sciences degree work: on spec. 10.02.20 “Comparative-historical, typological and comparative linguistics” / O. V.Grebneva. – Kazan, 2004. – 20 p. Longman Dictionary of Contemporary English. Available at https://www.ldoceonline Longman Essential Activator. Available at https://www.twirpx.com/file/287462/ 5. Olenchuk O. G. Language tools for the presentation of a problematic modality: dis. abstract for the Candidate of Philological Sciences degree work: on spec. 10.02.19 “Theory of language” / G. Olenchuk. – Izhevsk, 2012. – 22 p. Selezneva N. A. Modal verbs usage for implementation of the scientific text functions. Available at https://www.pglu.ru/upload/iblock/1e4/uch_2008_ii_00019.pdf Terre D. A. Language expressions with the modal lexemes необходимо, нужно, должен / must, ought to, have to: dis. abstract for the Candidate of Philological Sciences degree work: on spec. 10.02.19 “Theory of language” / D. A. Terre. – Tver 2006. – 20 p. Tsinovaya M. V. The typology of models with the verb must on the structural-semantical level (on the material of the English technical sublanguages) / M. V. Tsinovaya // Odessa: Scientific Bulletin of the International Humanitarian University. Series “Phylology”. – № 14. – 2015. Vasilieva L. V. The modal verb must and its functional equivalents as a segment of functional semantic field of modality: dis. abstract for the Candidate of Philological Sciences degree work: on spec. 10.02.04 “Germanic languages” / L. V. Vasilieva. – M., 1990. – 16 p. Vdovina M. V. Interaction of categories of modality, time, and form in the English sentences with modal verbs): dis. abstract for the Candidate of Philological Sciences degree work: on spec. 10.02.04 ‘Germanic languages’ / M. V. Vdovina. – S.-Petersburg, 2012. – 22 p. 5th Edition of Webster’s New World Colleage Dictionary. Available at https://sites.google.com/.../downloadpdfebook978/-pdf-webs... -